2019
DOI: 10.1186/s40880-019-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual prognostic role of 2‐oxoglutarate‐dependent oxygenases in ten cancer types: implications for cell cycle regulation and cell adhesion maintenance

Abstract: Background Tumor hypoxia is associated with metastasis and resistance to chemotherapy and radiotherapy. Genes involved in oxygen-sensing are clinically relevant and have significant implications for prognosis. In this study, we examined the pan-cancer prognostic significance of oxygen-sensing genes from the 2-oxoglutarate-dependent oxygenase family. Methods A multi-cohort, retrospective study of transcriptional profiles of 20,752 samples of 25 types of cancer was perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Several studies have suggested that PLOD2 is correlated with poor prognosis of multiple cancers, including sarcoma, lung cancer, renal cell carcinoma, breast cancer, cervical cancer and bladder cancer [19,[27][28][29][30][31]. PLOD2 reinforces the migration capacity of cancer cells, and also promotes cancer cells migration along the "highway" linear collagen [19,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that PLOD2 is correlated with poor prognosis of multiple cancers, including sarcoma, lung cancer, renal cell carcinoma, breast cancer, cervical cancer and bladder cancer [19,[27][28][29][30][31]. PLOD2 reinforces the migration capacity of cancer cells, and also promotes cancer cells migration along the "highway" linear collagen [19,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PLOD genes was observed to be elevated in clear cell renal cell carcinoma (ccRCC) when compared with normal kidney tissues, and genetic mutations of PLOD genes were presented in ~3% ccRCC tissues. Furthermore, they found that mRNA of PLOD genes was positively associated with the prognosis of ccRCC patients, while the expression pattern of PLOD genes in gastric cancer was different from those in ccRCC [ 14 ]. The expression of the PLOD family was also increased in gastric cancer compared with normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study assessed the expression and prognostic value of PLOD1/2/3 in wild-type and genetically mutated clear cell renal cell carcinoma (ccRCC) patients. Compared with the paired normal kidney tissues, ccRCC tissues expressed notably high PLOD1/2/3 mRNA and protein [ 14 ]. Here, high-level PLOD1/2/3 expression was strongly linked to advanced pathological tumor stage and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…In support of a pro-oncogenic role in cancer, high JMJD5 expression has been correlated with increased metastasis, invasiveness and poor survival in breast, colorectal, prostate, and oral cancers [112][113][114][115]. Conversely, a multi-cohort retrospective study across ten cancer types has suggested that JMJD5 may function as a tumour suppressor; high expression levels were associated with a lower risk of death in pancreatic and liver cancer cohorts, while low JMJD5 levels correlated with poorer survival outcomes [116]. In fact, JMJD5 was originally identified in a tumour suppressor gene screen [93].…”
Section: Og-oxygenases: Disease Mediatorsmentioning
confidence: 99%